a =\(\dfrac{3}{5}\)x\(\dfrac{4}{7}\)x\(^{1\dfrac{1}{2}}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, - \(\dfrac{2}{5}\) + \(\dfrac{4}{5}\).\(x\) = \(\dfrac{3}{5}\)
\(\dfrac{4}{5}\).\(x\) = \(\dfrac{3}{5}\)+ \(\dfrac{2}{5}\)
\(\dfrac{4}{5}\).\(x\) = 1
\(x\) = \(\dfrac{5}{4}\)
b, - \(\dfrac{3}{7}\) - \(\dfrac{4}{7}\): \(x\) = \(\dfrac{2}{5}\)
\(\dfrac{4}{7}\): \(x\) = - \(\dfrac{3}{7}\) - \(\dfrac{2}{5}\)
\(\dfrac{4}{7}\): \(x\) = - \(\dfrac{29}{35}\)
\(x\) = \(\dfrac{4}{7}\): (- \(\dfrac{29}{35}\) )
\(x\) = - \(\dfrac{20}{29}\)
c, \(\dfrac{4}{7}\).\(x\) + \(\dfrac{2}{3}\) = - \(\dfrac{1}{5}\)
\(\dfrac{4}{7}\).\(x\) = -\(\dfrac{1}{5}\) - \(\dfrac{2}{3}\)
\(\dfrac{4}{7}\).\(x\) = - \(\dfrac{13}{15}\)
\(x\) = - \(\dfrac{13}{15}\): \(\dfrac{4}{7}\)
\(x\) = - \(\dfrac{91}{60}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,2\dfrac{1}{2}-x+\dfrac{4}{5}=\dfrac{2}{3}-\left(-\dfrac{4}{7}\right)\\ \Rightarrow\dfrac{5}{2}-x+\dfrac{4}{5}=\dfrac{26}{21}\\ \Rightarrow\dfrac{5}{2}-x=\dfrac{46}{105}\\ \Rightarrow x=\dfrac{433}{210}\\ b,-\dfrac{4}{7}-x=\dfrac{3}{5}-2x\\ \Rightarrow2x-\dfrac{4}{7}-x=\dfrac{3}{5}\\ \Rightarrow2x-x=\dfrac{41}{35}\\ \Rightarrow x=\dfrac{41}{35}\\ c,\left(\dfrac{3}{8}-\dfrac{1}{5}\right)+\left(\dfrac{5}{8}-x\right)=\dfrac{1}{5}\\ \Rightarrow\dfrac{7}{40}+\dfrac{5}{8}-x=\dfrac{1}{5}\\ \Rightarrow\dfrac{4}{5}-x=\dfrac{1}{5}\\ \Rightarrow x=\dfrac{3}{5}.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: x+2/5=1/2
=>x=1/2-2/5=5/10-4/10=1/10
b; x-2/5=2/7
=>x=2/7+2/5=10/35+14/35=24/35
c: 3/5-x=1/10
=>x=3/5-1/10=6/10-1/10=5/10=1/2
d: x*3/4=9/20
=>x=9/20:3/4=9/20*4/3=36/60=3/5
e: x:1/7=14
=>x=14*1/7=2
f: =>x+1/4=2/5:1/2=4/5
=>x=4/5-1/4=16/20-5/20=11/20
g: =>x*2/3=9/12+2/3=3/4+2/3=9/12+8/12=17/12
=>x=17/12:2/3=17/12*3/2=51/24=17/8
![](https://rs.olm.vn/images/avt/0.png?1311)
a, 2/5 + 3/4 : x = -1/2
3/4 : x = -1/2 - 2/5
3/4 : x = -9/10
x = 3/4 : -9/10
x = -5/6
b, 5/7 - 2/3 . x = 4/5
2/3 . x = 4/5 + 5/7
2/3 . x = 53/35
x = 53/35 : 2/3
x = 159/70
![](https://rs.olm.vn/images/avt/0.png?1311)
\(3\dfrac{1}{2}+4\dfrac{5}{7}-5\dfrac{5}{14}\)
= \(\dfrac{7}{2}+\dfrac{33}{7}-\dfrac{75}{14}\)
= \(\dfrac{49}{14}+\dfrac{66}{14}-\dfrac{75}{14}\)
= \(\dfrac{40}{14}=\dfrac{20}{7}\)
\(4\dfrac{1}{2}+\dfrac{1}{2}\div5\dfrac{1}{2}\)
=\(\dfrac{9}{2}+\dfrac{1}{2}\div\dfrac{11}{2}\)
=\(\dfrac{9}{2}+\dfrac{1}{2}\times\dfrac{2}{11}\)
=\(\dfrac{9}{2}+\dfrac{1}{11}\)
=\(\dfrac{101}{22}\)
\(x\times3\dfrac{1}{3}=3\dfrac{1}{3}\div4\dfrac{1}{4}\)
\(x\times\dfrac{10}{3}=\dfrac{10}{3}\div\dfrac{17}{4}\)
\(x\times\dfrac{10}{3}=\dfrac{10}{3}\times\dfrac{4}{17}\)
\(x\times\dfrac{10}{3}=\dfrac{40}{51}\)
\(x=\dfrac{40}{51}\div\dfrac{10}{3}\)
\(x=\dfrac{40}{51}\times\dfrac{3}{10}\)
\(x=\dfrac{120}{510}=\dfrac{12}{51}=\dfrac{4}{7}\)
\(5\dfrac{2}{3}\div x=3\dfrac{2}{3}-2\dfrac{1}{2}\)
\(\dfrac{17}{3}\div x=\dfrac{11}{3}-\dfrac{5}{2}\)
\(\dfrac{17}{3}\div x=\dfrac{7}{6}\)
\(x=\dfrac{17}{3}\div\dfrac{7}{6}\)
\(x=\dfrac{17}{3}\times\dfrac{6}{7}\)
\(x=\dfrac{102}{21}=\dfrac{34}{7}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: x=4/27-2/3=4/27-18/27=-14/27
b: =>3/4x-1/4x=1/6+7/3
=>1/2x=1/6+14/6=5/2
hay x=5
c: =>13/10x=7/2+5/2=6
=>x=13/10:6=13/60
d: (3x+2)(-2/5x-7)=0
=>3x+2=0 hoặc 2/5x+7=0
=>x=-2/3 hoặc x=-35/2
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(A=\dfrac{-7}{28}\cdot\dfrac{15}{25}=\dfrac{-1}{4}\cdot\dfrac{3}{5}=\dfrac{-3}{20}\)
b: \(B=\dfrac{-5\cdot7}{14\cdot\left(-3\right)}=\dfrac{35}{42}=\dfrac{5}{6}\)
c: \(C=\dfrac{-1}{5}-\dfrac{1}{5}\cdot\dfrac{3}{5}=\dfrac{-1}{5}-\dfrac{3}{25}=\dfrac{-8}{25}\)
d: \(D=\dfrac{-3}{4}-\dfrac{1}{4}=-1\)
e: \(E=\dfrac{-4}{5}\left(1-\dfrac{15}{16}\right)=\dfrac{-4}{5}\cdot\dfrac{1}{16}=\dfrac{-1}{20}\)
f: \(F=\dfrac{6-7}{4}\cdot\dfrac{4+12}{22}=\dfrac{-1}{4}\cdot\dfrac{8}{11}=\dfrac{-2}{11}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\dfrac{2}{5}-x=\dfrac{1}{4}\)
\(x=\dfrac{2}{5}-\dfrac{1}{4}\)
\(x=\dfrac{8}{20}-\dfrac{5}{20}\)
\(x=\dfrac{3}{20}\)
\(b,\dfrac{4}{7}-x=\dfrac{1}{3}\)
\(x=\dfrac{4}{7}-\dfrac{1}{3}\)
\(x=\dfrac{12}{21}-\dfrac{7}{21}\)
\(x=\dfrac{5}{21}\)
\(c,\dfrac{7}{5}-x=\dfrac{2}{3}\)
\(x=\dfrac{7}{5}-\dfrac{2}{3}\)
\(x=\dfrac{21}{15}-\dfrac{10}{15}\)
\(x=\dfrac{11}{15}\)
#\(Toru\)
\(a>\)
\(\dfrac{2}{5}-x=\dfrac{1}{4}\)
\(x=\dfrac{2}{5}-\dfrac{1}{4}\)
\(x=\dfrac{3}{20}\)
\(b>\)
\(\dfrac{4}{7}-x=\dfrac{1}{3}\)
\(x=\dfrac{4}{7}-\dfrac{1}{3}\)
\(x=\dfrac{5}{21}\)
\(c>\)
\(\dfrac{7}{5}-x=\dfrac{2}{3}\)
\(x=\dfrac{7}{5}-\dfrac{2}{3}\)
\(x=\dfrac{11}{15}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x=7-\dfrac{2}{5}+1,62=8,22x=7−52+1,62=8,22
b) x=4 \dfrac{3}{5}+\dfrac{1}{5}-\dfrac{1}{2}=4 \dfrac{3}{10}x=453+51−21=4103
c) 2 x-x=\dfrac{3}{5}+\dfrac{4}{7}2x−x=53+74
x=\dfrac{41}{35}x=3541
d) x=3 \dfrac{1}{2}-\dfrac{5}{7}+\dfrac{1}{13}-0.25x=321−75+131−0.25
x=2 \dfrac{223}{364}x=2364223
x=7-\dfrac{2}{5}+1,62=8,22x=7−52+1,62=8,22
b) x=4 \dfrac{3}{5}+\dfrac{1}{5}-\dfrac{1}{2}=4 \dfrac{3}{10}x=453+51−21=4103
c) 2 x-x=\dfrac{3}{5}+\dfrac{4}{7}2x−x=53+74
x=\dfrac{41}{35}x=3541
d) x=3 \dfrac{1}{2}-\dfrac{5}{7}+\dfrac{1}{13}-0.25x=321−75+131−0.25
x=2 \dfrac{223}{364}x=2364223
`3/5xx4/7xx1 1/2`
`=12/35xx3/2`
`=18/35`